2014
DOI: 10.1016/j.atmosenv.2014.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and hypertensive disorders of pregnancy: A systematic review and meta-analysis

Abstract: Hypertensive disorders of pregnancy (HDP, including gestational hypertension, preeclampsia, and eclampsia) have a substantial public health impact. Maternal exposure to high levels of air pollution may trigger HDP, but this association remains unclear. The objective of our report is to assess and quantify the association between maternal exposures to criteria air pollutants (ozone, carbon monoxide, nitrogen dioxide, sulfur dioxide, and particulate matter ≤ 10, 2.5 μm) on HDP risk. PubMed, EMBASE, MEDLINE, Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 56 publications
1
71
0
1
Order By: Relevance
“…Our findings are consistent with the results of 2 previous meta-analyses that summarized the associations between air pollution exposure during pregnancy and pregnancy-induced hypertensive disorders. 35, 36 Pedersen et al found that pregnancy-induced hypertensive disorders were significantly associated with a 5 μg/m 3 increment in PM 2.5 (OR=1.57; 95% CI: 1.26-1.96), a 10-μg/ m 3 increment in NO 2 (OR=1.20; 95% CI: 1.00-1.44), and a 10 μg/m 3 increment in PM 10 (OR=1.13; 95% CI: 1.02-1.26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with the results of 2 previous meta-analyses that summarized the associations between air pollution exposure during pregnancy and pregnancy-induced hypertensive disorders. 35, 36 Pedersen et al found that pregnancy-induced hypertensive disorders were significantly associated with a 5 μg/m 3 increment in PM 2.5 (OR=1.57; 95% CI: 1.26-1.96), a 10-μg/ m 3 increment in NO 2 (OR=1.20; 95% CI: 1.00-1.44), and a 10 μg/m 3 increment in PM 10 (OR=1.13; 95% CI: 1.02-1.26).…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous meta-analysis observed the significant associations of hypertensive disorder of pregnancy with CO and O 3 exposure during the pregnancy. 36 For example, a 1 ppm increase in average CO exposure during the first trimester was associated with a 79% (95% CI: 31%-145%) increase in the risk of hypertensive disorder during pregnancy. 36 These results indicate that more research is needed in the future to confirm the possible effects of CO, O 3 , SO 2 , and NO x on hypertension.…”
Section: 50mentioning
confidence: 99%
“…Indeed, 2 recent metaanalyses suggest heterogeneity in the association between air pollution and various pregnancy hypertensive disorders (10,11), among which gestational hypertension (GH) is common but has received less research attention. Specifically, given that only 3 (12)(13)(14) of 17 studies in one meta-analysis (10) reported specific data on GH, no synthesis could be derived for this outcome separately.…”
mentioning
confidence: 99%
“…Several studies which modelled prenatal exposure found a reduction in birth weight [23,24,26] however two studies negated the association [25,27]. Due to the lack of clarity and the methodology short comings of some studies [20][21][22][23][24]26] there is a need for additional evidence on the subject of air pollution and pregnancy.…”
Section: Air Pollution and Pregnancymentioning
confidence: 99%
“…Exposure to nitrogen dioxide during the entire pregnancy has been associated with a risk of pregnant woman developing pre-eclampsia [20,21]. Furthermore proximity to a major road has also been associated with pre -term birth [21,22].…”
Section: Air Pollution and Pregnancymentioning
confidence: 99%